The Process of Reframing Music Education at the University of Education Linz (Pedagogical Horizons, 2017)
In this paper the process of reframing music education at the University of Education Linz will be discussed as an interdisciplinary contribution to University development from an educational-psychological and didactical angle. The importance of productive interrelations between educational and other sciences and team development for raising the quality of University teaching is highlighted. To achieve this, the team development process that took place from 2012 to 2015 is analysed regarding its (1) initial focus, (2) methods and approaches, (3) milestones and (4) results. Besides theoretical grounding, explicit references to Musical Inquiry Learning (Waid, 2016a) and new study programmes giving students the opportunity to put strong emphasis on music education are introduced as key results of the reframing process. Additional hints for initiating, leading and evaluating processes of team development in the context of teacher education are given, resulting in educational-psychological implications for a Positive Educational Psychology.
Keywords: University development; Educational Psychology; Music Education; Didactics; Team development